Use of Integrase-Minus Lentiviral Vector for Transient Expression - Hossein Azadeh; Nader Mansour Samaei; Ghasem Janbabai; Mohammad Reza Haghshenas; Hossein Khanahmad Shahreza; Touraj Farazmandfar (Cell Journal, 2012)
Objective: Lentivirus-derived vectors are among the most promising viral vectors for gene therapy which is currently available, but their use in clinical practice is limited due to associated risk of insertional mutagenesis. Gene targeting is an ideal method for gene therapy, but it has low efficiency in comparison to viral vector methods. In this study, we are going to design and construct an integrase-minus lentiviral vector. This vector is suitable for transient expression of gene and gene targeting with viral vector.Materials and Methods: In this experimental study, three missense mutations were induced in the catalytic domain of Integrase gene in the pLP1 plasmid and resulted D64V, D116A and E152G changes in the amino acid sequence through site directed mutagenesis. The pLenti6.2-GW/EmGFP transfer vector, associated with native and mutated packaging mix, was transfected into 293T cell line. In order to titer the lentivirus stock, the viruses were harvested. Finally, the viruses transduced into COS-7 cell line to assess green fluorescent protein (GFP) gene expression by a fluorescence microscopy.Results: Recombinant and wild lentiviruses titer was about 5~8×106 transducing units/ml in COS-7 cell line. The number of GFP-positive cells transduced with native viruses was decreased slightly during two weeks after viral transduction. In contrast, in the case of integrase-minus viruses, a dramatic decrease in the number of GFP positive cells was observed.Conclusion: This study was conducted to overcome the integration of lentiviral genome into a host genome. Nonintegrating lentiviral vectors can be used for transient gene expression and gene targeting if a Target gene cassette is placed in the lentivirus gene structure. This combination method decreases disadvantages of both processes, such as random integration of lentiviruses and low efficiency of gene targeting.